KNOWLEDGE OF THE RURAL GENDER: SCIENTIFIC REFERENCE POINTS - Iulia BEJAN VOLC (Akademos: Revista de Ştiinţă, Inovare, Cultură şi Artă, 2015)
The article is a synthesis of the gender studies specificity, denotes aspirations of social actors (studious young people), reflects family everyday life situations, highlights the relation „parents – children” and characterizes the image of superior members of rural families. The paper reflects a number of socio-cultural and socio-psychological situations showing the relationship among family members, thus, gender studies remain full of explanatory and valuable judgments formed within social and cultural behavioral models. Methods and techniques of gender studies contributed to the understanding of the way gender shapes our lives, ideas and attitudes. The paradigm „scientific heritages” allows demystifying erroneous concepts, relations and systems in gender studies theory and practice.